2009
DOI: 10.1254/jphs.09195fp
|View full text |Cite
|
Sign up to set email alerts
|

The C-Terminal Region of Serotonin Transporter Is Important for Its Trafficking and Glycosylation

Abstract: Abstract. We investigated the effects of brefeldin A and ilimaquinone, inhibitors of membrane trafficking, using serotonin transporter (SERT)-expressing COS-7 cells. Both drugs significantly inhibited the serotonin uptake activity of SERT and caused SERT to be retained in the endoplasmic reticulum (ER), indicating that membrane trafficking is an important factor for SERT functional regulation. In agreement with previous reports, a C-terminal-deletion mutant of SERT (SERTΔCT) mostly localized to the ER and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 50 publications
4
35
0
Order By: Relevance
“…A band with a molecular size of approximately 63 kDa (arrowhead) was identified as the form of SERT that is modified by high-mannose-type oligosaccharides, which is the immaturely glycosylated SERT that is retained in the ER. Our previous study also demonstrated that bands with molecular sizes greater than 80 kDa correspond to oligomers of immaturely glycosylated SERT (18,37). As shown in Fig.…”
Section: -Pba Increased Maturely Glycosylated Sert and Decreased Immsupporting
confidence: 56%
See 4 more Smart Citations
“…A band with a molecular size of approximately 63 kDa (arrowhead) was identified as the form of SERT that is modified by high-mannose-type oligosaccharides, which is the immaturely glycosylated SERT that is retained in the ER. Our previous study also demonstrated that bands with molecular sizes greater than 80 kDa correspond to oligomers of immaturely glycosylated SERT (18,37). As shown in Fig.…”
Section: -Pba Increased Maturely Glycosylated Sert and Decreased Immsupporting
confidence: 56%
“…Previously, we examined whether proteasome inhibition affects the uptake activity and membrane trafficking of SERT (18). We found that proteasome inhibition caused SERT to be retained in the ER, which resulted in ER stress due to impaired membrane trafficking.…”
Section: Effects Of the Chemical Chaperone 4-phenylbutylate On The Fumentioning
confidence: 99%
See 3 more Smart Citations